Use of oxidized regenerated cellulose (Surgicel Nu-Knit) as a hemostat in laparoscopic endometriotic cystectomy: a case report - Sharma, J. B.; Zangmo, Rinchen; Kumar, Sunesh; Roy, K. K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Ovary is one of the common sites for occurrence of endometriosis. Endometriosis contributes to a major cause of infertility in young women. Apart from infertility, endometriosis is one of the important causes of severe secondary dysmenorrhea and chronic pelvic pain. Endometriotic cystectomy is often required in endometriotic cysts more than 3 cm in size. A 33 year old patient married for 4 years with primary infertility was diagnosed to have an endometriotic cyst of the ovary measuring 4x3 centimeters. Patient underwent laparoscopic endometriotic cystectomy under general anesthesia. Intraoperatively, the right ovary was enlarged and was adherent to the posterior surface of uterus and the uterosacral ligament of the same side. Adhesiolysis was done followed by removal of the ovarian endometriotic cyst. Post cystectomy oozing was controlled by application of Oxidized regenerated cellulose (Surgicel Nu-Knit) on the bleeding points. Postoperative course of the patient was uneventful and she was discharged after 7 hours in stable condition.